Secure Software Engineering Education: Knowledge Area, Curriculum and Resources - Xiaohong Yuan; Li Yang; Bilan Jones; Huiming Yu; Bei-Tseng Chu (Journal of Cybersecurity Education, Research & Practice)
This paper reviews current efforts and resources in secure software engineering education, with the goal of providing guidance for educators to make use of these resources in developing secure software engineering curriculum. These resources include Common Body of Knowledge, reference curriculum, sample curriculum materials, hands-on exercises, and resources developed by industry and open source community. The relationship among the Common Body of Knowledge proposed by the Department of Homeland Security, the Software Engineering Institute at Carnegie Mellon University, and ACM/IEEE are discussed. The recent practices on secure software engineering education, including secure software engineering related programs, courses, and course modules are reviewed. The course modules are categorized into four categories to facilitate the adoption of these course modules. Available hands-on exercises developed for teaching software security are described and mapped to the taxonomy of coding errors. The rich resources including various secure software development processes, methods and tools developed by industry and open source community are surveyed. A road map is provided to organize these resources and guide educators in adopting these resources and integrating them into their courses.